The significance of religious experience - Wettstein, Howard K. (New York ; Oxford : Oxford University Press, 2012)
This text is a collection of essays on the philosophy of religion by Howard Wettstein, who is a widely respected analytic philosopher. Over the past 20 years, Wettstein has attempted to reconcile his faith with his philosophy, and he brings his personal investment in this mission to the essays collected here.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Religion -- Philosophy; Experience (Religion)